Odorless, convenient and one-pot synthesis of thioethers from organic halides and thiourea. (4th March 2019) - Monfared, Aazam; Ahmadi, Sheida; Rahmani, Zahra; Nezhad, Parvaneh Delir Kheirollahi; Hosseinian, Akram
ABSTRACT: This review summarizes the most important advances in the synthesis of thioethers via the reaction of organic halides with thiourea as an odorless and nontoxic sulfur source during the period 2005 to May 2018. The reactions have been classified based on the type of catalysts. GRAPHICAL ABSTRACT: